PENGGUNAAN OLAH RAGA DAN PERMAINAN TRADISIONAL SENTANI SEBAGAI MEDIA PENGEMBANGAN KARAKTER ANAK-ANAK - Yektiningtyas, Wigati; Rinantanti , Yulini; Haay , Christine (LPPM Uncen, 2023)
Sentani people are rich in cultural heritages, one of which is traditional sports/games (TSG) which Sentani children no longer recognize. Preservation and socialization need to be done to avoid its extinction. This activity is one of the initiatives to reintroduce TSG to Sentani children. The purpose of this service activity is to (a) introduce TSG to children in Yokiwa Village; (b) teach TSG to children in Yokiwa Village; (c) engage children to socialize, recognize, and learn the character of their peers through exercising/playing. This activity involved around 25 children from Yokiwa Village aged 8-12 years. Besides, the instructors and parents of Yokiwa village (20 people) were involved. Activities were carried out at the obae (meeting place) and its yard between May-June 2023. This service used participation method and collaboration among lecturers and students. The members of the community service worked together with the students to carry out the TSG and did an evaluation of the material to be used in learning. In practice, the service members were directly involved in the introduction and practice of TSG and related them to the development of children's character. The results of this activity showed (1) the children recognized their ancestor's TSG, (2) the children liked to play TSG, and (3) the children learned that in exercising/playing TSG they needed patience, mutual cooperation, hard work, sportivity, discipline, thoroughness as well as cooperation. Keywords: traditional sports; traditional games; Sentani community; preservation; character development